Structural characterizations, thermal behavior, and electrical measurements of the amidosulfonic acid catalyzed thermal ring-opening polymerization of substituted cyclotriphosphazene in 1,2,4-trichlorobenzene solution - Koran, Kenan; Gorgulu, Ahmet Orhan (Wiley-Hindawi, 2018)
In this study, we aimed to design and synthesize poly[3,3,5,5-tetrachloro-1,1-bis{spiro(2 ',2 ''-dioxy-1 '-1 ''-biphenylyl)}phosphazene] (3) in order to obtain a polymer which is resistant to moisture and hydrolysis and also contains chlorine atoms within its structure. For this reason, the polymerization experiments of polymer 3 were performed using ring-opening polymerization (ROP) of 3,3,5,5-tetrachloro-1,1-bis[spiro(2 ',2 ''-dioxy-1 ',1 ''-biphenylyl)]cyclotriphosphazene (2) at different time and temperature. In particular, ROP of 2 was successful in 1,2,4-trichlorobenzene solution in the presence amidosulfonic acid and promoter (CaSO4.2H(2)O) in sealed glass tubes under vacuum for 60, 72, and 96 hr at 220 degrees C. The changes in molecular weight and molecular weight distribution of the polymer 3 were noted as a function of polymerization reaction time. The structure of polymer 3 was approved by gel permeation chromatography (GPC), FT-IR, NMR spectroscopy (P-31, H-1, C-13), and elemental analysis. The glass transition temperature (T-g) and thermal stability of polymer 3 were determined using differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA), respectively. Dielectric properties of 3 were determined as a function of frequency at five different temperatures by an impedance analyzer. The activation energy of polymer 3 was calculated using Flynn-Wall-Ozawa (F-W-O) integral method.
Keywords: activation energy; dielectric constant; dielectric property; polyphosphazene; ring-opening polymerization